Evaluation of eating attitudes of nursing students for type-2 diabetes and cardiovascular diseases - Özpancar, Nurhan; Bulantekin Düzalan, Özlem; Vardar İnkaya, Bahar; Olgun, Nermin (Progress in Nutrition, 2019)
Eating disorders/attitudes might lead to disrupted metabolic control. When body releases insulin insufficiently and irregularly, this causes the blood glucose level to rise. Abnormal eating attitudes and behaviors, which develop especially during adolescence, are acknowledged to be the strongest precursor to eating disorders at later ages. The study aimed to evaluate eating attitudes of nursing students with regard to the risk of type 2 diabetes and cardiovascular diseases. This study was designed as a descriptive. The sample contained 356 volunteers. The data were collected using A Questionnaire For The Risk Of Type 2 Diabetes (FINDRISC), the Cardiovascular Disease Risk Factors Knowledge Level Scale (CARRF-KL) and the Eating Attitudes Test (EAT) and various measurements such as waist circumference measurement, blood pressure measurement and body mass indeks. The mean scores on the CARRF-KL Scale suggested a statistically significant difference between the students of different grades. Additionally, the students’ scores on the FINDRISC were significantly correlated with their weight, body mass index, waist circumferences, family history of diabetes or heart disease, and level of exercising. The findings suggest that higher weight and body mass indexes and larger waist circumferences lead to a corresponding increase in the scores on the FINDRISC and pose a risk in terms of type 2 diabetes and that higher educational status means a higher knowledge level about cardiovascular diseases.